PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) BERBANTUAN MEDIA GOOGLE SITES UNTUK MENINGKATKAN KETRAMPILAN BERPIKIR KRITIS PADA MATA PELAJARAN IPAS - Supriyanto, Agus; Nasrullah, Muhammad; Novi Puspita, Anang; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research explores how combining Problem-Based Learning (PBL) with Google Sites can enhance the critical thinking of fifth-grade IPAS students. Addressing the limitations of teacher-centered instruction, the study used a qualitative classroom action research approach. After two cycles of implementation, students showed a 55.56% increase in their ability to analyze data and draw conclusions. The integration of Google Sites not only supported the PBL framework but also significantly increased student participation. Ultimately, this approach proved successful in developing essential analytical skills at the elementary level